CHANGES IN PHYSICAL AND CHEMICAL PROPERTIES OF ORAL FLUID IN PATIENTS WITH PERIODONTAL DISEASES IN THE SETTINGS OF CHRONIC HEPATITIS C DURING ANTIVIRAL THERAPY - H.A. Sichkoriz; L.Yu. Minko (Ukrainian Medical Stomatological Academy, 2016)
The results represent the study of changes in physical and chemical properties of oral fluid in 31 people with chronic hepatitis C (CHC) who received antiviral treatment (AVT). It was found that the changes in physical and chemical properties of oral fluid were more pronounced in patients with periodontal diseases (PD) in the settings of chronic hepatitis C during antiviral therapy compared with patients without the history of CHC. The increase in violations of these parameters is observed on the 1st-3rd months of AVT and characterized by decreased rate of stimulated secretion and increased viscosity of the mixed saliva, shift of acid-base balance toward acidosis and reduced buffer capacity. The negative dynamics of physical and chemical properties of oral fluid during AVT requires correction to prevent the development of PD and reduce the number of complications. Introduction. Published data indicate a significant increase in the prevalence of HCV-infection and high incidence of periodontal lesions in the settings of infection with hepatitis C. Many authors point to the relationship of the occurrence and complicated course of periodontal diseases with impaired physical and chemical properties of oral fluid in patients with chronic hepatitis C. The latter changes contribute to disturbances of homeostasis in the oral cavity causing the development of hyposalivation, which is clinically manifested by xerostomia. The development of xerostomia occurs due to feedback inhibition of salivary gland function during AVT of infectious diseases. Such peculiarities of clinical course of PD in patients with CHC during AVT and few scientific data on the impact of antiviral treatment on periodontal tissues determine the relevance of studying the changes in physical and chemical parameters of oral fluid in these patients. The objective of our study was to examine changes in physical and chemical properties of oral fluid in patients with periodontal diseases in the settings of chronic hepatitis C during antiviral therapy. Materials and methods. For the objective estimation of changes in physical and chemical properties of the oral fluid of CHC patients during AVT we studied the dynamics of changes of physical-chemical parameters of oral fluid in 31 patients who underwent antiviral treatment. After recording the volume of collected saliva the rate of salivation was measured (ml/min) to determine the rate of stimulated salivation. The viscosity of oral fluid was determined with Ostwald viscometer. Measuring pH of newly collected oral fluid was performed with pH-metermillivoltmeter pH-150m (UK). The evaluation of buffer capacity of saliva was carried out by the respective test strips (Saliva-Check Buffer) of GCSaliva Check test system. Results and discussion. The dynamics of changes of studied oral fluid parameters during AVT is presented by increased deviation in the early stages of treatment and their normalization in the long term results. Thus, deceleration of salivation by 14.65% (from 1.57±0.01 ml/min to 1.34±0.01 ml/min, p<0.001) was detected a month after the start of AVT. 3 and 6 months after the rate of stimulated secretion in CHC patients was 1.33±0.01 and 1.38±0.01 ml/min. The latest parameters of 1.64±0.01 ml/min (12-18 months) demonstrate the normalization of salivation approaching the norm. The viscosity of the oral fluid within a month of treatment of CHC and PD increased: by 3.05% (from 1.97±0.02 mPa×s to 2.03±0.01 mPa×s, p<0.01). 3 months after treatment parameters of oral fluid viscosity in patients decreased. The long term results of oral fluid viscosity in the study group in 6 and 12-18 months were 1.85±0.001 mPa×s and 1.54±0.001 mPa×s. The shift of oral fluid pH toward acidosis was detected one month after the beginning of AVT. Thus, the pH decreased significantly (from 6.45±0.01 to 6.41±0.004, p<0.001). The pH began to rise beginning with the 3rd month compared with levels of the 1st month after treatment. However, the pH was still significantly lower than the level before treatment (6.43±0.004 vs. 6.45±0.01, P<0.001). In the period of 12-18 months after AVT the rate increased by 4.81% (up to 6.76±0.003). 1 month after the beginning of AVT the buffer capacity of oral fluid decreased: by 21.83% (from 7.65±0.21 to 5.97±0.16, p<0.001). The recovery of buffer capacity of oral fluid occurred 3 months after, which is reflected in significant (p<0.01) parameter increase (up to 6.19±0.11 points). The parameters continue rising after treatment in the long term results. Conclusions: • It was established that pronounced changes in physical and chemical properties of oral fluid occur on the 1st-3rd months of AVT in CHC patients and they are characterized by the decreased rate of stimulated secretion by 14.65%, increased viscosity of mixed saliva by 3.05%, significant shift of acid-base balance toward acidosis and reduced buffer capacity by 21.83%. • Deviations of physical and chemical properties of oral fluid in patients with periodontal diseases in the settings of CHC during antiviral treatment increase, mostly triggering the local periodontal-pathogenic mechanism and requiring an obligatory correction to prevent the development of periodontal diseases and complications. The prospect of further research is the study of additional parameters of the homeostasis of oral cavity: oral habitat and imbalance of immunocompetent systems in the patients with periodontal diseases in the settings of CHC during AVT increasing the treatment efficacy of PD by improving complex therapeutic approaches in these patients.